Impact of land legislation in Sarawak: politics and its legislative trends / Ahmad Bakhtiar Hamdan, Ahmad Dzufadzli, Nur ‘Asyiqin Ahmad - Hamdan, Ahmad Bakhtiar; Hamdan, Ahmad Dzufadzli; Ahmad, Nur ‘Asyiqin (2007)
This paper is entitled "Impact of Land Legislation in Sarawak: Politics and its Legislative Trends". It is aimed at analyzing the development of land related legislations that have been passed by the Sarawak Legislative Assembly, since its inauguration till date. The analysis will also include the impact of the numerous amendments made to the ordinances and the Sarawak Land Code. Then, this paper seeks to highlight probable reasons that fuelled the initiative to amend the legislations.